„Medicamenten-Kastens“ from 1850.: „Medicamenten-Kastens“ from 1850. - Habek, Dubravko; Habek, Roko (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
The paper presents the content of the basic medicine box "Medicamenten-Kastens" from 1850 for military units according to the original document of the Vienna court office with a discussion. It contained 8 utensils for mensuration, dispensing and application of medicinal substances and 28 substances in the form of 22 "simplicia" and 4 "composita" and 2 bases for medicinal preparations. Topical disinfectants and hemostyptics, expectorants, analgospasmolytics, emetics, purgatives and digestives from the contents of this mobile military pharmacy were a component of the pharmacopoeias of the time, which were proclaimed for the areas of the Habsburg Monarchy, including the Croatian regions.